Sistem Pemanenan Air hujan dengan Metode Roof Harvesting System untuk Kebutuhan Non Domestik - Samsul Arifin; Henny Pratiwi Adi; Abdul Rochim (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The increasing need for clean water in urban areas, including Salatiga City, is a major challenge along with population growth and climate change. One alternative solution is a rainwater harvesting system using the Roof Harvesting System (RHS) method. This study aims to analyze the potential amount of rainwater that can be harvested, determine the optimal capacity of the reservoir, and design a suitable RHS system for non-domestic needs in the KH. Hasyim Asy'ari Building, Campus 3 UIN Salatiga.This study uses a quantitative method with a descriptive approach. The research stages include collecting primary data through direct observation and measuring the roof area. Then collecting secondary data in the form of annual rainfall data and related literature. The last calculation of rainwater potential. The results showed that the roof area of ​​the building was 2,756.81 m², with a catchment area of ​​1,626.89 m², it can capture rainwater with an optimal volume of 9,371 liters/day. Considering the annual rainfall pattern in Salatiga City, the optimal capacity of the recommended reservoir is 6 water tanks with a volume of 1,550 liters each, so the total capacity is 9,300 liters. Non-domestic water needs reach 9,552.68 liters/day, which means that this rainwater harvesting system can meet around 98% of daily needs, with the potential for integration of additional water sources to cover the shortfall. The proposed Roof Harvesting System design includes an initial filtration system, distribution pipe network, and reservoir, with periodic maintenance to ensure the quality of water that can be used for non-domestic needs. The implementation of this system has the potential to reduce dependence on conventional water sources and support the concept of a green campus and sustainable water management.